CircSLC8A1 Acts as a Tumor Suppressor in Prostate Cancer via Sponging miR-21. (2nd April 2021) - Wang, Daoyuan; Yan, Shuxian; Wang, Lihui; Li, Yunlong; Qiao, Baoping
Abstract : Background. There is more and more evidence showed that circRNAs played essentially role in the regulation of various biological processes. The role of circSLC8A1 in prostate cancer (PCa) is yet little known. Methods. The CircSLC8A1 expression in human prostate cancer was measured by qRT-PCR. The interplay between the specific circRNA, miRNA, and mRNA was investigated by RT-PCR and luciferase reporter assay. Through transient transfection of siRNA, the impacts of circSLC8A1 on PCa were discussed. Cell cycle evaluation, transwell assay, and CCK-8 assay were employed to determine its biological influences. Results. In this study, our data revealed that circSLC8A1 was downregulated in PCa tissues and cells. The reduction of circSLC8A1 resulted in the inhibition of cell proliferation and migration. In mechanism, circSLC8A1 exhibited a direct interaction with miR-21 and displayed as a miRNA sponge to inhibit PCa progression. The functional analysis revealed that the circSLC8A1/miR-21 axis may regulate the cell proliferation, angiogenesis, cell migration, epithelial to mesenchymal transition, MAPK signaling pathway, and chemokine signaling pathway. Conclusions. CircSLC8A1 functioned as an inhibitor of neoplasm via modulating the miR-21 and might serve as a prospective target for the treatment of PCa.